2022
DOI: 10.3389/fpls.2022.952877
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization and analysis of Golden 2-Like transcription factors related to leaf chlorophyll synthesis in diploid and triploid Eucalyptus urophylla

Abstract: Golden 2-Like (GLK) transcription factors play a crucial role in chloroplast development and chlorophyll synthesis in many plant taxa. To date, no systematic analysis of GLK transcription factors in tree species has been conducted. In this study, 40 EgrGLK genes in the Eucalyptus grandis genome were identified and divided into seven groups based on the gene structure and motif composition. The EgrGLK genes were mapped to 11 chromosomes and the distribution of genes on chromosome was uneven. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…It was indicated that the genome size and the number of NAC family members are not always related. We suspected that some EuNAC genes were lost during evolution, and similar evolutionary loss events occurred in the WRKY and GLK transcription factor family ( Liu et al., 2021 ; Liu et al., 2022 ). The diversity in the number of NAC gene family members in different species may be influenced genome duplication events, such as whole-genome duplication, segmental duplication, or tandem duplication ( Zhang, 2003 ; Chang and Duda, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that the genome size and the number of NAC family members are not always related. We suspected that some EuNAC genes were lost during evolution, and similar evolutionary loss events occurred in the WRKY and GLK transcription factor family ( Liu et al., 2021 ; Liu et al., 2022 ). The diversity in the number of NAC gene family members in different species may be influenced genome duplication events, such as whole-genome duplication, segmental duplication, or tandem duplication ( Zhang, 2003 ; Chang and Duda, 2012 ).…”
Section: Discussionmentioning
confidence: 99%